Competitive Saturation in Makassar’s Coffee Shop Industry: A Phenomenological Inquiry Into Business Actors’ Experiences - Muh Al Fatah Arief Putra; Andi Aryani Hardiyanti; Tuti Adi Tama; Risnawati (Economics and Business Journal (ECBIS), 2026)
This study examines the rapid expansion of the coffee shop industry in Makassar City as a phenomenon that creates not only economic opportunities but also increasing competitive saturation. As coffee shops in Makassar have developed beyond places of beverage consumption into urban social spaces linked to lifestyle, sociability, symbolic visibility, and identity formation, competition has become denser and more complex. The study aims to gain an in-depth understanding of how coffee shop owners and managers experience, interpret, and respond to this increasingly crowded market. Using a qualitative phenomenological approach, the research employed in-depth semi-structured interviews with business actors involved in strategic and operational decision-making, supported by contextual observation and business-related documents. The findings reveal five main themes: market growth is experienced as both opportunity and pressure; similarity among coffee shops increases vulnerability and reduces perceived distinctiveness; entrepreneurs rely on continuous adaptation rather than fixed strategies; business sustainability is understood as stability, relevance, and survival rather than expansion alone; and competition is shaped not only by product and price, but also by ambience, visibility, symbolic value, and lifestyle alignment.